LANGUAGE VARIATIONS IN DEPOK: A STUDY OF LINGUISTIC LANDSCAPE AND DIALECTOLOGY - Munawarah, Sri; Datang, Frans Asisi (International Review of Humanities Studies, 2019)
Written languages are present in various media in public landscapes, such as notice boards, banners, or bumper stickers. Studying these simple signs is the starting point in observing how a language variety exists and interacts with other languages. It is interesting to study how the instances of written texts found in public landscapes can be an indicator of what language variety is actually used by the inhabitants of Depok. Based on its history and its geography, a hypothesis states that many speakers of Betawi language and Sundanese reside in Depok. The study is aimed at demonstrating the written language varieties found in Depok public landscapes based on written evidence which are compared with language varieties based on the regional variation (dialectology). This qualitative study used the sociogeolinguistic approach combining sociolinguistics, linguistic landscape, and dialectology (geolinguistics). The results show there are two language use distributions in Depok, the Sundanese and the Betawi language. From the landscapes, Betawi language is used in billboards, restaurant signboards, and local government banners. The study is useful for the local government in their efforts to confirm the identity of Depok people.